Thermoelectric properties of copper chalcogenide alloys deposited via the solution-phase using a thiol–amine solvent mixture. Issue 102 (20th October 2016) - Ma, Yuanyu; Vartak, Prathamesh B.; Nagaraj, Prajwal; Wang, Robert Y.
Abstract : We use soluble precursors to deposit Cu2− x Se y S1− y and Ag-doped Cu2− x Se y S1− y thin films. We report the effects of Cu vacancies, Ag doping, and Se : S ratio on the thermoelectric properties at room temperature. Abstract : There has been a growing interest in solution-phase routes to thermoelectric materials due to the decreased costs and novel device architectures that these methods enable. Many excellent thermoelectric materials are metal chalcogenide semiconductors and the ability to create soluble metal chalcogenide semiconductor precursors using thiol–amine solvent mixtures was recently demonstrated by others. In this paper, we report the first thermoelectric property measurements on metal chalcogenide thin films made in this manner. We create Cu2− x Se y S1− y and Ag-doped Cu2− x Se y S1− y thin films and study the interrelationship between their composition and room temperature thermoelectric properties. We find that the precursor annealing temperature affects the metal : chalcogen ratio, and leads to charge carrier concentration changes that affect the Seebeck coefficient and electrical conductivity. Increasing the Se : S ratio increases electrical conductivity and decreases the Seebeck coefficient. We also find that incorporating Ag into the Cu2− x Se y S1− y film leads to appreciable improvements in thermoelectric performance by increasing the Seebeck coefficient and decreasing thermal conductivity. Overall, we find that the room temperature thermoelectric properties of these solution-processed materials are comparable to measurements on Cu2− x Se alloys made via conventional thermoelectric material processing methods. Achieving parity between solution-phase processing and conventional processing is an important milestone and demonstrates the promise of this binary solvent approach as a solution-phase route to thermoelectric materials.